PENGARUH MASASE ENDORPHIN TERHADAP TINGKAT KECEMASAN DAN INVOLUSIO UTERI IBU NIFAS - Sri Rahayu; Melyana Nurul Widyawati; Retno Kusuma Dewi (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
One of factor in the failure of the breastfeeding process is maternal anxiety. Anxiety during breastfeeding will block the letdown reflex so that milk production decreases. The Efforts to reduce gold can be done with endorphin massage. Other benefits of breastfeeding more often will accelerate uterine involution. The aim of the study was to analyze the effect of endorphin massage on anxiety and the process of involuntary uterine maternal uterine. This type of research is quasi-experimental with a pre-post test with control group design. The population is all normal postpartum mothers in District 1 and 2 District Health Centers in Grobogan District. The sample number of treatment group 13 and control group 13 was taken by simple random sampling. Data analysis with Independent t- test. For the control group, care was taken according to the standards in service, namely counseling for postpartum mothers on how to breastfeed, massage of uterine fundus. The results of the study before treatment most of the respondents experienced moderate anxiety (69%), and average fundal uteri height of 10.5 cm. The independent t test showed that there was an effect of endorphin massage on anxiety level (p value = 0.001) and there was no effect on uterine involution (p value = 0.302). Endorphin massage done by husbands to postpartum mothers contributes very well in reducing maternal anxiety, increasing self-confidence for the need to be socialized to the community, especially postpartum mothers and husbands to always be able to cooperate and support each other for the health and welfare of mothers and babies.